Feeding a blend of thymol and carvacrol to coccidiosis challenged broilers: effect on performance and gut health - Niknia, AD; Vakili, R; Palangi, V (Journal of the Hellenic Veterinary Medical Society, 2025)
Performance and gut health of coccidiosis-challenged broilers were investigated using thymol and carvacrol in their diet. A completely randomized design was used in the experiment. There were three phases of feeding for the chickens: starters (1-10 days), growers (11-24 days) and finishers (25-42 days). It was found that chicks were split into three experimental groups: 1) negative control diets without challenges or additives; 2) positive control diets with Eimeria tenella challenges and without additives; and 3) diets with mentioned challenge and thymol and carvacrol (0.01 g/kg). Experimental groups consisted of five replicates, each with 12 chicks. As part of the trial, body weight gain (BWG), feed intake (FCR), and coccidial lesion scores were assessed in two birds/replicate, which were selected randomly and euthanized by cervical dislocation. When thymol and carvacrol were blended, the results indicated improved BWG and FCR (P<0.05) when compared to PC. Supplementing the diet with phytogenic essential oil increased the percentage of beneficial bacteria in the ileum, including lactobacilli and bifidobacteria, while decreasing the number of pathogenic E.coli bacteria (P<0.05). Compared with PC-treated birds, birds with coccidiosis treated with essential oils had longer and wider villus, deeper crypts, and more goblet cells (P<0.05). Including this additive in PC diet suppressed intestinal lesion scores (P<0.05). Because the NC group was not exposed to the challenge, it caused the highest BWG and lowest FCR scores, the best microflora in the ileum, optimal villus growth, and the least intestinal lesion scores in birds. Researchers concluded that coccidiosis-challenged birds with high levels of carvacrol and thymol experienced improved performance and gut health (P>0.05).